2021
DOI: 10.3389/fimmu.2021.772304
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation in Chronic Lymphocytic Leukemia and Other Blood Cancers

Abstract: In the past decade, aberrant O-GlcNAcylation has emerged as a new hallmark of cancer. O-GlcNAcylation is a post-translational modification that results when the amino-sugar β-D-N-acetylglucosamine (GlcNAc) is made in the hexosamine biosynthesis pathway (HBP) and covalently attached to serine and threonine residues in intracellular proteins by the glycosyltransferase O-GlcNAc transferase (OGT). O-GlcNAc moieties reflect the metabolic state of a cell and are removed by O-GlcNAcase (OGA). O-GlcNAcylation affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 217 publications
(367 reference statements)
0
11
0
1
Order By: Relevance
“…Bulk AML cells show enhanced HBP activity and O-GlcNAcylation compared t0 PBMCs and chemotherapeutic drugs have been shown to further enhance O-GlcNAcylation in AML cells ( 19 , 22 , 23 ). In this manuscript, we use bulk cells to refer to MNC from blood or bone marrow in AML patients and AML blasts to refer to non-LSC AML cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulk AML cells show enhanced HBP activity and O-GlcNAcylation compared t0 PBMCs and chemotherapeutic drugs have been shown to further enhance O-GlcNAcylation in AML cells ( 19 , 22 , 23 ). In this manuscript, we use bulk cells to refer to MNC from blood or bone marrow in AML patients and AML blasts to refer to non-LSC AML cells.…”
Section: Resultsmentioning
confidence: 99%
“…Increased O-GlcNAcylation is implicated in both hematopoietic and solid cancers where it controls cell proliferation and metastasis ( 17 , 18 ). O-GlcNAcylation is a key player in hematological malignancies such as chronic lymphocytic leukemia (CLL), pre-B-cell acute lymphocytic leukemia (preB ALL) and AML ( 19 ). Specific O-GlcNAcylation of signal transducer and activator of transcription 5 (STAT5) at threonine 92 has been reported both in CLL and AML cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that hyper O-GlcNAcylation seems to be a common feature in a variety of cancers, including liver cancer, 35,177 breast cancer, 13 uterine cancer, 178 prostatic cancer, 179 colorectal cancer 180 and pancreatic cancer, 94,181 and even non-solid cancers such as acute myeloid leukaemia and other blood cancers. 26,182 Hyper O-GlcNAcylation in cancer cells is mainly attributed to disruption of O-GlcNAcylation cycle homeostasis and abnormal expression of its process enzymes. 183 The proteins and involved are described in Figure 8.…”
Section: Hypero-glcnacylation Is Linked To the Pathologic Hallmarks O...mentioning
confidence: 99%
“…In addition to solid tumors, there are many reports about the role of O -GlcNAcylation in various blood cancers (Spaner 2021 ). Shi et al (Shi et al 2010 ) reported increased O -GlcNAcylation and OGT in chronic lymphocytic leukemia (CLL) cells compared with those in normal lymphocytes, and also revealed that this is caused by higher levels of the sugar donor UDP-GlcNAc.…”
Section: O -Glcnac and Cancermentioning
confidence: 99%